Directed Energy Deposition of Multi-Principal Element Alloys - Sreeramagiri, Praveen; Balasubramanian, Ganesh (Frontiers in Materials, 2022)
As efforts associated with the exploration of multi-principal element alloys (MPEAs) using computational and data-intensive methods continue to rise, experimental realization and validation of the predicted material properties require high-throughput and combinatorial synthesis of these alloys. While additive manufacturing (AM) has emerged as the leading pathway to address these challenges and for rapid prototyping through part fabrication, extensive research on developing and understanding the process-structure-property correlations is imminent. In particular, directed energy deposition (DED) based AM of MPEAs holds great promise because of the boundless compositional variations possible for functionally graded component manufacturing as well as surface cladding. We analyze the recent efforts in DED of MPEAs, the microstructural evolution during the laser metal deposition of various transition and refractory elements, and assess the effects of various processing parameters on the material phase and properties. Our efforts suggest that the development of robust predictive approaches for process parameter selection and modifying the synthesis mechanisms are essential to enable DED platforms to repeatedly produce defect free, stable and designer MPEAs.